OPTIMAL CONDITIONS FOR FORMATION OF STUDENTS' CREATIVE ACTIVITY IN THE LEARNING PROCESS IN HIGH SCHOOL (Pedagogy of Higher and Secondary Education, 2009)
The optimal inner and outward conditions of high school students' creative activity are being considered in the article.